2006
DOI: 10.1590/s0004-282x2006000400003
|View full text |Cite
|
Sign up to set email alerts
|

Saccadic movements using eye-tracking technology in individuals with autism spectrum disorders: pilot study

Abstract: -Objective: To verify diff e rences in the visual scanning strategies between pervasive developmental disorders (PDD) and controls when they are observing social and non-social picture s . M e t h o d : PDD group (PDDG) comprised by 10 non-re t a rded subjects (age from 4 to 41) and age-matched contro l group (CG). Nine social pictures with human beings (including two pictures of cat mask), and 3 nonsocial p i c t u res of objects were presented for 5 seconds. Saccadic movements and fixation were re c o rded w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 20 publications
(8 reference statements)
1
11
0
3
Order By: Relevance
“…Nevertheless, there were differences when the game was stopped (see Table 6), since the clinical group fixed their gaze on the bottom of the screen, as shown in several research cases. This indicator can help professionals ascertain how to display new elements or concepts to them [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there were differences when the game was stopped (see Table 6), since the clinical group fixed their gaze on the bottom of the screen, as shown in several research cases. This indicator can help professionals ascertain how to display new elements or concepts to them [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…Ashwin, Ricciardelli, & Baron-Cohen, 2009). Indeed previous work using eye-tracking techniques has indicated that ASD individuals spend less time than do typical individuals viewing people and faces in social situations (Mercadante, Macedo, Baptista, Paula, & Schwartzman, 2006;Riby & Hancock, 2009;Riby & Hancock, 2008), and future work would be valuable in utilising these eye tracking techniques to examine the role of directed attention on salient social and person aspects of an event and its effect on subsequent memory recall in an eyewitness paradigm. That the ASD group were significantly more accurate for Surrounding details when interviewed with SIs is not unexpected given that these types of details can be relatively separated from person and action details and might rely on more of a rote memory strategy.…”
Section: Insert Tablementioning
confidence: 99%
“…Orsati et al 19 came to the same conclusion, despite the small size of the sample. Data obtained point to the necessity of new studies with a higher number of participants 19,27 . Concerning decision-making, Postma et al published a research that demonstrates the use of Mobile Eye in the analysis of vision in decision-making processes.…”
Section: Resultsmentioning
confidence: 98%
“…Mercadante et al 27 assessed the search and visual focus pattern in autistic patients compared to a group control of healthy subjects, concluding autistic subjects present search and focus patterns of images that in certain aspects configure peculiar social situations. Orsati et al 19 came to the same conclusion, despite the small size of the sample.…”
Section: Resultsmentioning
confidence: 99%